ENHANCING ORAL COMMUNICATION ABILITIES VIA THE TALKING STICK MODEL SUPPORTED BY VISUAL MEDIA IN PRIMARY EDUCATION - Tri Yulinda Riskawati (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This study aimed to enhance speaking skills in grade III pupils during the even semester of the 2023/2024 academic year using the talking stick model supplemented by visual media. This study had two cycles, each consisting of four stages: preparation, activity, observation, and reflection. The research duration was two months, from May to June 2024, with 19 participants, comprising 12 boys and 7 girls, from grade III of SDN Bandar 02, located in Bandar District, Batang Regency, Central Java Province. Methods of data gathering include test sheets, observation, and documentation. The study's results indicated a substantial enhancement in the speaking abilities of third-grade kids. The class averages for learning outcomes demonstrate a progression: Pre-Cycle = 65.80, Cycle I = 77.80, and Cycle II = 83.00. Thus, it can be stated that implementing the Talking Stick model in the educational process enhances students' speaking abilities and replies